Terrorism as reflected in Joseph Conrad’s the secret agent: A sociological approach - Raden Muhammad Ali; Aria Candramukti (UAD TEFL International Conference)
Nowadays, there are so many people talking and discussing what we called terrorism. However, most of us still do not have sufficient insight related to the kinds, motivations, and purposes of terror attacks. This paper is aimed to find the types of terror attack as reflected in The Secret Agent by Joseph Conrad and to show the causes of terror as reflected in the novel. The researchers apply descriptive qualitative as the method of analyzing the data. Some of the research findings are as follows. First, the terror attacks found in the novel are physical and mental. Second, the causes of terror are political and economic.